Singaporean Swear Words Used in Hokkien Dialect - Sugiantari, Putu Ayu Dinda; Budasi, I Gede; Mahendrayana, Gede (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
The study was conducted using a descriptive qualitative approach, focusing on the use of swear words by Singaporeans visiting the Canggu district. The objectives of this research were to identify the swear words, analyze their forms, determine their functions, and examine their references. Primary data were collected through interviews, with the researcher serving as the main instrument. Additional instruments included an interview sheet and a questionnaire. The data collection process involved gathering, reducing, displaying, drawing conclusions, and verifying findings. The study identified 33 swear words used by Singaporeans. In terms of form, these swear words were categorized into words (7), phrases (21), and clauses (5). Their functions included expressing emotions (10), drawing attention (5), aggression (13), social identity (7), and regressive behavior (6). Furthermore, the references of these swear words were associated with conditions (14), devils (2), objects (3), body functions (5), activities (5), and kinship (4). The results of this study provide insight into how Singaporeans incorporate swear words into daily conversations. This knowledge can be valuable for language acquisition, cultural analysis, and enhancing communication in multilingual settings.